On wings of eagles [videorecording (DVD)] - Fiennes, Joseph, 1970-; Dou, Xiao, 1988-; Arends, Elizabeth (Sony Pictures Home Entertainment, 2016)
Eric Liddell, China's first gold medalist and one of Scotland's greatest athletes, returns to war-torn China.